Perception and impact of pain in the lives of elderly patients with oncological diseases - João Evangelista da Costa; Clélia Albino Simpson; Ana Elza Oliveira de Mendonça; Deyla Moura Ramos Isoldi; Rayanne Suelly da Costa Silva; Nayanne Ricelli da Costa Silva (Universidade Federal do Ceará, 2016)
Objective: to understand the impact and changes in the routine of family relationships caused by pain in elderly patients with oncological diseases. Methods: it is a qualitative research based on oral history of life. Study participants were five elderly of the Nucleus of Hemotherapy and Hematology. Criteria of Inclusion were being assisted by the treatment team, in cancer treatment during the study period and being 60 years old or more. Results: data were collected through semi-structured interviews and analyzed using content analysis. Conclusion: it was shown that the pain caused feelings of sadness and isolation, changing the lives of the elderly and their families. Cancer and pain produced physical and psychological repercussions, affecting their lives. The success for the treatment of pain depends on the work of professionals to make the complete identification of complaints, selecting strategies and evaluating them.